SINTESIS DAN KARAKTERISASI SIFAT MAGNETIK NANOKOMPOSIT Fe3O4 – MONTMORILONIT BERDASARKAN VARIASI SUHU - Pintor Simamora; Krisna Krisna (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
This study aims to investigate the characteristics of the magnetic properties of Fe3O4 – Montmorillonite nanocomposite and determine the effect of temperature on the characteristics of Fe3O4 – Montmorillonite nanocomposite. Fe3O4 - Montmorillonite nanocomposite were synthesized using coprecipitation method. Synthesis is done by mixing iron sand with HCl as solvent and NH4OH as a precipitant. The results of the precipitate is then washed repeatedly with distilled water and dried in an oven. Furthermore, the Fe3O4 nanoparticles powder mixed into the montmorillonite which has been diluted with water and then stirred with a magnetic stirrer and heated at temperature variation 40°C, 70°C, and 100°C, then NaOH was added dropwise to 100 ml of water and then washed with aquades and dried in an oven. The resulting nanocomposite characterized by using X-Ray Diffractometer (XRD) to determine the size and content of the crystal phase and Vibrating Sample Magnetometer (VSM) formed to determine magnetic properties of materials. From the test results of X-Ray Diffractometer (XRD) to indicate the size of the crystal Fe3O4 Nanoparticles 34.8691 nm. And Vibrating Sample Magnetometer (VSM) test results values ​​obtained magnetic saturation (Ms) for Fe3O4 nanoparticle samples of 52.15 emu/gr and for the nanocomposite sample at 40°C, 70°C and 100°C values ​​obtained Magnetic saturation (Ms ) is 3.365 emu/gr, 4.635 emu/g, and 4.75 emu/g. While the coercivity field (Hc) of each sample is 0.0102 T, 0.0112 T, and 0.0136 T. From these results it can be concluded that the higher the temperature of the nanocomposite which varied the higher the value of magnetic saturation and field koersivitasnya so the magnetic properties of these materials will be even greater. Keywords: nanocomposite, Fe3O4, montmorillonite, coprecipitation.